A comparative analysis of four activated clotting time measurement devices in cardiac surgery with cardiopulmonary bypass. (September 2021) - Li, Han; Serrick, Cyril; Rao, Vivek; Yip, Paul M
Background: In cardiac surgery on cardiopulmonary bypass (CPB), heparin anticoagulation is monitored by point-of-care measurement of activated clotting time (ACT). The objective of this study was to compare four ACT systems in cardiac surgery in terms of their reproducibility, agreement and potential clinical impact at relevant medical decision points. Methods: The study included 40 cardiac surgery patients. Samples were taken at five time points before (T1), after heparinization for CPB (T2, T3, T4), and after heparin reversal (T5). The reproducibility, correlation, and differences in ACT values were assessed with two devices from each of the four ACT systems: Instrumentation Laboratory Hemochron Elite (Hmch), Medtronic HMS Plus (HMS), Abbott i-STAT, and Helena Abrazo. Subrange analyses were performed for low ACT values (results from T1, T5) and high ACT values (results from T2, T3, T4). Results: Within-system analysis showed strong linear correlation between paired measurements (R = 0.968-0.993). However, Hmch showed poorer reproducibility with highest proportion of values that exceed a difference of 10% and highest overall standard error of 74 seconds across the measurement range compared to that of the others (range 39-47 seconds, respectively). For inter-system comparison, using Hmch as reference, ACTs were strongly correlated as follows: HMS (R = 0.938), i-STAT (R = 0.911), and Abrazo (R = 0.911). Agreement analysis in the high ACT range showed HMS tended to have higher ACT values with +11% bias over Hmch, whereas i-STAT (–8% bias) and Abrazo (–13% bias) tended to underestimate. Post-protamine ACT results were dependent on device type where Hmch yielded highest post-protamine ACT (+13% higher than baseline) compared to –16% for HMS, –10% for iSTAT and 0% for Abrazo. Conclusions: Each device had individual reproducibility and biases, which may impact peri-operative heparin management. Careful validation must be undertaken when adopting a different method as decision limits would be affected. Clinicians should also be cautious using ACT as the only indicator for full heparin reversal.